Exploring Algerian Higher Education Classroom Discourse: Verbal Abuse Manifestations and its Impacts on Learners of English - Boudjelal, Mustapha (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
The very mentioning of verbal abuse is more likely to send the reader/listener to educational settings like the primary, middle, and high schools. Howbeit, it is rare to affiliate between this linguistic maltreatment and higher education settings. The aim of this study is to explore EFL university learners’ experiences of verbal abuse by means of investigating the various effects of verbal abuse on classroom participation, academic achievements and self-esteem. This study is based on the reflection of nine female master learners from the University of Mostaganem of their verbal abuse experiences. The data have been collected from a survey questionnaire that comprises different sections, involving closed and open-ended questions. The results showcase that learners tend to experience verbal abuse at the university, articulated by some teachers in a form of shaming and public criticizing, which mainly targets their “English language abilities”. As to its effects, it has been found that due to learners’ age (over 20years old), verbal abuse does not negatively affect learners’ motivation, self-esteem, and academic achievements; however, it tends to reduce their classroom participation rate.